2020
DOI: 10.1186/s12936-020-03401-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of peer-learning assisted primary school students educating the rural community on insecticide-treated nets utilization in Jimma-zone Ethiopia

Abstract: Background Making insecticide-treated nets (ITNs) utilization a social norm would support the global goal of malaria eradication and Ethiopian national aim of its elimination by 2030. Jimma zone is one of the endemic settings in Ethiopia. This study aimed to report effects of malaria education, delivered by students, on community behaviours; particularly ITNs. Methods In pre-posttest, cross-sectional household surveys conducted in rural villages of 5 districts in Jimma Zone, Ethiopia, 762 households were sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Recent studies revealed the burden of malaria in school-age children, their role in acting as a reservoir of infection, and the least likelihood of SAC in utilizing insecticide-treated nets (ITNs) [4][5][6]. e effectiveness of LLITNs in malaria control and the role of schools have been demonstrated [7][8][9][10][11]. While earlier studies have surveyed LLITN usage among school children and school-based net distribution in the integrated national malaria surveillance system [5,12], there is a paucity of information on the impact of LLITN usage on malaria prevalence among school-age children in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed the burden of malaria in school-age children, their role in acting as a reservoir of infection, and the least likelihood of SAC in utilizing insecticide-treated nets (ITNs) [4][5][6]. e effectiveness of LLITNs in malaria control and the role of schools have been demonstrated [7][8][9][10][11]. While earlier studies have surveyed LLITN usage among school children and school-based net distribution in the integrated national malaria surveillance system [5,12], there is a paucity of information on the impact of LLITN usage on malaria prevalence among school-age children in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…This revealed that ITN programme should also focus on promoting ITN utilization behaviour through different strategies. School-centered community education strategy promoted ITN utilization [ 37 , 39 ]. Concurrently, the SS equivalent (SSP6) was 92.1% producing only 7.9% behavioural failure to use ITN.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to have the correct knowledge towards malaria because it helps individuals understand the ways in which malaria is transmitted, the cause of malaria, the source of malaria and the signs and symptoms towards malaria so that they may know how to prevent contracting the disease. As author aware, there have been several intervention studies to improve KAP of malaria in other African countries, including Nigeria (12), South Africa (13), North Sudan (14), Ethiopia (15), Niger (16), Mali (17), and Malawi (18). In Guinea, however, there has yet to be an intervention study conducted on the KAP of malaria.…”
Section: Introductionmentioning
confidence: 99%